(untitled) (Current Horticulture, 2024)
Climate change is a major threat to biodiversity, impacting on horticultural crops, due to erratic temperature regime, rainfall, more demand for water and enhanced abiotic stresses. Changes in plant phenology are one of the earliest responses to rapid global climate change and could potentially have serious consequences for fruit crops that depend on temperature and rainfall. However, the changes are not be only harmful, as CO2 concentration may enhance faster photosynthesis and increased temperature may hasten the process of fruit maturity. An increasing temperature affects photosynthesis directly, causing alterations in sugars, organic acids, and flavonoids contents, firmness and antioxidant activity. Hence, there is a need to protect these valuable crops for sustainability against the climate change scenario. Temperature is a primary factor affecting the rate of plant growth and development; therefore, it influences the life-cycle of fruit plants in various ways. The low temperature kills the plant tissues by freezing. Whereas, most plant tissues can be destroyed by freezing temperatures suddenly imposed during a period of growth and development. In freeze susceptible plant tissues, free water freezes forming crystals that disrupt cell membranes, whereas in freeze-resistant tissues the water is bound in the form of hydrophilic colloids. Pollination is also most sensitive phenological stages to temperature extremes. During such developmental stages, temperature extremes would greatly affect fruit production. Adverse effect of high temperature can be seen during both vegetative and reproductive growth stages in various fruit crops. The changes in gene expression that occur with cold acclimation contribute to increased freezing tolerance. The proper method of frost/freeze protection must be chosen by each crop for a particular site. Therefore, the latest scientific information regarding climate change impact on physiology of fruit crops under varied climatic conditions has been discussed.